Bovine trichomoniasis: A hidden threat to reproductive efficiency - Herry Agoes Hermadi; Aswin Rafif Khairullah; Yenny Damayanti; Erma Safitri; Wiwiek Tyasningsih; Sunaryo Hadi Warsito; Kartika Afrida Fauzia; Bantari Wisynu Kusuma Wardhani; Fitrine Ekawasti; Syahputra Wibowo; Ima Fauziah; Ikechukwu Benjamin Moses; et al. (Open Veterinary Journal)
Bovine trichomoniasis is a reproductive illness that affects cattle causing pyometra, early to mid-pregnancy miscarriages, and lower birth rates. Tritrichomonas foetus is a flagellated protozoan which first discovered in France in 1888, and compsosts three phases during its lifecycle including trophozoite, cyst, and pseudocyst. In addition, several factors contributed to prevalence of trichomoniasis and fall into three categories are management, cow, and bull-related factors. The fundamental causes of bovine trichomoniasis-related embryonic or fetal death have not been precisely determined. Immunity to T. foetus has been subjected to very little contemporary research, but a thorough assessment of earlier work has been conducted. Clinical symptoms in cattle ranged from moderate endometritis or vaginitis to acute inflammation of entire reproductive system. In cows, pregnancy-related infections result in metritis, pyometra, early embryonic demise, and abortion; whereas in bulls, it suspected that bovine trichomoniasis should have their preputial cavity sampled and then sent to a lab for positive organism identification. To date, sexual contact is the known method of transmission of T. foetus. There haven't been any significant attempts to create a treatment plan for cows because infection is of self-limitation. The distinct epidemiological features of bovine trichomoniasis determine the best prevention and control measures. [Open Vet J 2024; 14(11.000): 2722-2730]